Lipid Peroxidation in Chronic Cerebral HypoperfusionInduced Neurodegeneration in Rats - S, Anil Kumar; SA, Saif; P, Oothuman; MIA, Mustafa (IIUM Medical Journal Malaysia, 2011)
Introduction: Reduced cerebral blood ﬂ ow is associated with neurodegenerative disorders and dementia, in particular. Experimental evidence has demonstrated the initiating role of chronic cerebral hypoperfusion in neuronal damage to the hippocampus, the cerebral cortex, the white matter areas and the visual system. Permanent, bilateral occlusion of the common carotid arteries of rats (two vessel occlusion - 2VO) has been introduced for the reproduction of chronic cerebral hypoperfusion as it occurs in Alzheimer’s disease and human aging. Increased generation of free radicals through lipid peroxidation can damage neuronal cell membrane. Markers of lipid peroxidation have been found to be elevated in brain tissues and body ﬂ uids in neurodegenerative diseases, including Alzheimer’s disease, Parkinson disease and amyotrophic lateral sclerosis. Materials and Methods: Malondialdehyde (MDA), ﬁnal product of lipid peroxidation, was estimated by thiobarbituric acid-reactive substances (TBARS) assay kit at eight weeks after induction of 2VO in the rats and control group. Results: Our study revealed a highly signiﬁ cant (p<0.001) increase in the mean MDA concentration (12.296 ± 1.113 μM) in 2VO rats as compared to the control group (5.286 ± 0.363 μM) rats. Conclusion: Therapeutic strategies to modulate lipid peroxidation early throughout the course of the disease may be promising in slowing or possibly preventing neurodegenerative disorders.